2005
DOI: 10.5326/0410221
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Asparaginase on a Combination Chemotherapy Protocol for Canine Multicentric Lymphoma

Abstract: Combination chemotherapy is superior to single-agent chemotherapy for treating canine lymphoma, but the effect of each drug on efficacy remains unknown. By comparing 34 dogs treated with a modified cyclophosphamide, vincristine, prednisone (COP) chemotherapy protocol and 42 dogs given asparaginase in the induction phase of the same protocol, the effect of asparaginase on the chemotherapeutic protocol was determined. Both groups were compared based on clinical response at 2 weeks and 6 weeks, and on the progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 18 publications
1
39
0
1
Order By: Relevance
“…For a majority of dogs in the MOPP group that received l-asparaginase, induction was performed with a combination of l-asparaginase and vincristine before moving on to a MOPP protocol, likely once T-cell immunophenotype was determined. In addition to the fact that l-asparaginase use was evaluated and found to be balanced between the groups, and it has been shown that l-asparaginase use does not significantly impact outcome including likelihood of remission or duration of progression-free interval, it is unlikely that it impacted the results in the current study (Jeffreys et al 2005, MacDonald et al 2005.…”
Section: Discussionmentioning
confidence: 83%
“…For a majority of dogs in the MOPP group that received l-asparaginase, induction was performed with a combination of l-asparaginase and vincristine before moving on to a MOPP protocol, likely once T-cell immunophenotype was determined. In addition to the fact that l-asparaginase use was evaluated and found to be balanced between the groups, and it has been shown that l-asparaginase use does not significantly impact outcome including likelihood of remission or duration of progression-free interval, it is unlikely that it impacted the results in the current study (Jeffreys et al 2005, MacDonald et al 2005.…”
Section: Discussionmentioning
confidence: 83%
“…[1][2][3][4][5][6][7][8][9] For patients in CR, various treatment strategies have been explored to eliminate minimal residual disease that could contribute to relapse. Such strategies included highdose chemotherapy with 10 or without 11 autologous bone marrow transplantation, standard-dose maintenance therapy, [1][2][3][4]6,9,12 chemoimmunotherapy, 13 half-body radiation therapy (HBRT), [14][15][16] or consolidation with new drug combinations. 17 The optimal dose, schedule, or number of cycles of maintenance or consolidation therapy for dogs who achieve CR has not been established.…”
mentioning
confidence: 99%
“…Canine malignant lymphoma is the most common haematopoietic cancer in dogs 16 . In this study, all three dogs were diagnosed with naturally occurring malignant lymphoma based on clinical presentation, physical examination and immunophenotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Canine lymphoma is the most common naturally occurring haematopoietic tumour in dogs 16 . In the more aggressive or high grade forms of lymphomas, the most common finding is painless enlargement of one or more peripheral lymph nodes although many dogs can be asymptomatic upon presentation.…”
Section: Introductionmentioning
confidence: 99%